Assessing Knowledge, Attitudes and Practices Towards COVID-19 Public Health Preventive Measures Among Patients at Mulago National Referral Hospital - Twinamasiko, Nelson; Olum, Ronald; Gwokyalya, Anna Maria; Nakityo, Innocent; Wasswa, Enock; Sserunjogi, Emmanuel (Risk management and healthcare policy, 2021)
COVID-19 has become a major global health challenge, with Uganda reporting over 20,000 cases. There is, however, a scarcity of data on the perception of patients in Uganda towards the highly infectious disease. We aimed to assess the awareness, knowledge, attitudes, and practices towards COVID-19 preventive measures among patients at Mulago National Referral Hospital (MNRH), Uganda. Methods: A cross-sectional quantitative survey was conducted in August, 2020, among patients in surgical and medical wards at MNRH. An interviewer-administered, pre-validated questionnaire was used to collect data that was entered into Google Forms and analyzed using Microsoft Excel and STATA 16. Descriptive statistics was used to present data from univariate analysis. Patients whose knowledge and practice scores were greater or equal to the average score were regarded to have good knowledge and practices respectively. Chisquare, Fisher’s Exact tests and binary logistic regression were used to assess factors associated with COVID-19 knowledge and practices. A P<0.05 was statistically significant. Results: Overall, 114 patients were approached and 102 consented to participate. Most were females (53.8%), aged above 45 years (31.4%) with 40.2% reporting primary level as the highest level of education. About 55.9% (n=57) had adequate knowledge for COVID-19 and its related practices, and 52% (n=53) had good COVID-19 related practices. Knowledge significantly differed by marital status at bivariate analysis (P=0.020), however this lost significance at logistic regression. Female patients were thrice more likely to have good COVID-19 prevention practices compared to males (COR: 2.59, 95% CI: 1.2 to 5.8, P=0.020). Some 47 (46.1%) participants perceived that COVID-19 preventive measures were not difficult at all to observe. Conclusion: About half of the patients at Mulago National Referral Hospital lack adequate knowledge and practice on COVID-19 prevention. Continued patient education is required to increase knowledge which will in turn improve adherence to COVID-19 preventive practices.
Keywords: COVID-19; Knowledge; Attitudes; Practices; Patients